Prevalence of rotator cuff tear in paraplegic patients compared with controls - Akbar, Michael; Balean, Gabriel; Brunner, Manuela; Seyler, Thorsten M.; Bruckner, Thomas; Munzinger, Judith; Grieser, Thomas; Gerner, Hans J.; Loew, Markus (The journal of bone & joint surgery. A, American volume, 2010)
Background: - Musculoskeletal injuries of the shoulder in paraplegic patients with long-term survival can result from overuse and/or inappropriate use of wheelchairs. The purpose of the present study was to evaluate the prevalence and risk of pathological changes in the weight-bearing shoulder girdle of paraplegic patients who have been wheelchair-dependent for more than thirty years in comparison with able-bodied volunteers. - Methods: - One hundred paraplegic patients were matched for sex and age with a group of 100 able-bodied volunteers. Two hundred shoulders from each group were evaluated with use of magnetic resonance imaging. Collected outcome measures included a standardized clinical examination protocol, the Constant score, and a visual analog score for pain intensity. - Results: - Shoulder function according to the Constant score was significantly worse in the paraplegic patients than in the able-bodied volunteers. Similarly, the visual analog scale pain scores were significantly worse for the paraplegic patients. Magnetic resonance imaging showed that the prevalence of rotator cuff tears in either shoulder was significantly higher in the paraplegic patients than in the able-bodied volunteers (63% compared with 15%), resulting in a tenfold higher risk of rotator cuff rupture among paraplegic patients. - Conclusions: - The present study demonstrates that the structural and functional changes of the shoulder joint are more severe and the risk of development of shoulder girdle damage is significantly higher in individuals with long-term paraplegia than in age-matched controls. - Level of Evidence: - Prognostic Level III. See Instructions to Authors for a complete description of levels of evidence.
Gesehen am 16.11.2022